Hereditary diffuse leucoencephalopathy with spheroids. Issue 9 (21st August 2003) - Hancock, N; Poon, M; Taylor, B; McLean, C
Abstract : Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare inherited progressive leucoencephalopathy characterised by giant neuroaxonal swellings (spheroids) within the CNS white matter. The case is reported of a 45 year old woman with a rapidly progressive fulminant illness course characterised by progressive cognitive decline with depressive features. A presumed dominant inheritance pattern was elicited. This report reviews the literature on HDLS and the relation of this disorder to other conditions with giant neuroaxonal swellings.